You've Been Pranked: Reality Tv, National Identity and the Privileged Status of Australian Children's Drama. Issue 1 (February 2013) - Potter, Anna
Australian children have always been considered a special television audience. In November 2009, Australia's public service broadcaster the ABC launched Australia's first dedicated free-to-air children's channel. Within a year of its launch, ABC3's most popular program was a local version of the transnational reality format, Prank Patrol . The popularity of reality television with children challenges policy settings, including the Children's Television Standards (CTS), that privilege drama in the expression of the goals of cultural nationalism. While public service broadcasting ideology is expressed and applied to Australian commercial free-to-air channels through the CTS, public service media compete with pay TV channels for the child audience using a range of genres. Thus contemporary Australian children's television is characterised by an abundance of supply, pan-platform delivery and a policy regime that has remained largely unchanged since the late 1970s.